Preparation of desymmetrised meso-tartrate derivatives - synthesis and utility of (R ',R ',R,S)-2,3-butane diacetal protected dimethyl tartrate - Dixon, D; Foster, A; Ley, S; Reynolds, D (1999)
The synthesis of 2,3-butane diacetal protected dimethyl tartrate (R',R',R,S)-l using a chiral memory protocol and its utility for the preparation of desymmetrised mesotartrate derivatives through selective transesterification and aminolysis of the spatially different carboxylate termini is described.